How Covid-19 has reinforced the importance of a numerate society. Issue 2 (3rd April 2021) - O'Sullivan, Kathy; O'Meara, Niamh; Goos, Merrilyn; Conway, Paul
Abstract : Our everyday lives have been transformed in 2020. Key features of this transformation have been the significance of COVID-related numeracy in our everyday lives and the realisation of the story it might tell about lives, health and death. In recent years, governments and educators around the world have been advocating for numeracy as an essential skill that people need to acquire in order to fully engage in society. Covid-19 led to the World Health Organisation declaring a global pandemic in March 2020 and this pandemic has since highlighted the importance of a numerate society in today's world. Paulos [Paulos, John Allen. 1988. Innumeracy: Mathematical Illiteracy and Its Consequences . New York: Hill & Wang.] states that innumeracy is widespread, even in our apparently well-educated society, and he outlines misconceptions in mathematical knowledge that may contribute to an innumerate society. The following article presents a conceptual paper which reflects on how numeracy plays a major role in society's understanding of the impact of a pandemic, such as Covid-19. This paper addresses issues such as proliferation of numeracy ideas, examples of innumerate commentary in the media and problems in society when citizens do not possess adequate numeracy skills to help them understand the issues that may arise in the face of a global pandemic.